Using ChatGPT to navigate ambivalent and contradictory research findings on artificial intelligence - Sohail, Shahab Saquib; Madsen, Dag Øivind; Himeur, Yassine; Ashraf, Maheen (Frontiers in Artificial Intelligence, 2023)
With the rapid development and integration of AI in various domains, understanding the nuances of AI research has become critical for policymakers, researchers, and practitioners. However, the results are vast and diverse and even can be contradictory or ambivalent, presenting a significant challenge for individuals seeking to grasp and synthesize the findings. This perspective paper discusses the ambivalent and contradictory research findings in the literature on artificial intelligence (AI) and explores whether ChatGPT can be used to navigate and make sense of the AI literature.